2021
DOI: 10.1002/jbio.202100242
|View full text |Cite
|
Sign up to set email alerts
|

Computational image translation from Mueller matrix polarimetry to bright‐field microscopy

Abstract: Mueller matrix (MM) polarimetry can provide comprehensive information about the polarization properties that are closely related to the microstructural features and has demonstrated its potential in biomedical studies and clinical practices, and bright-field microscopy is widely used in pathological diagnosis as the golden standard. In this work, we improve the throughput of MM microscopy by learning a statistical transformation between these two imaging systems based on deep learning. Using this approach, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It was shown that machine learning approach (ML) can enhance the contrast in polarimetric images of tissue at micro-scale [72,73] and also help the diagnostic interpretation of the wide-field polarimetric images of brain tissue [74].…”
Section: Brain Fiber Tracking For Assisting Neurosurgerymentioning
confidence: 99%
“…It was shown that machine learning approach (ML) can enhance the contrast in polarimetric images of tissue at micro-scale [72,73] and also help the diagnostic interpretation of the wide-field polarimetric images of brain tissue [74].…”
Section: Brain Fiber Tracking For Assisting Neurosurgerymentioning
confidence: 99%
“…They have different imaging principles, and each has its advantages. In previous studies, we proposed a cross-modality transformation from MM microscopy images to bright-field microscopy images 23 based on a conditional generative adversarial network (cGAN) 24 without changing the optical path design. However, to obtain a MM image, four exposures of the dual division of the focal plane (DoFP) polarimeter-based system 25 are required, which will be affected by light intensity fluctuations and co-registration of polarimetric images for imaging quality 26 .…”
Section: Introductionmentioning
confidence: 99%